Contraste medioambiental del crecimiento económico, una evaluación econométrica de la curva ambiental de Kuznets mediante técnicas de umbral - Castillo Ochoa, Dennys Alexander (2023)
The world economy multiplied almost fivefold in the last fifty years, and due to this excessive growth it had an enormous cost for the environment (Organization of the United Nations, 2019). Such is the case that, in 2016, air pollution alone cost the world economy 5.7 trillion dollars, or the equivalent of 4.8% of world GDP (World Bank, 2016). Therefore, based on this problem, the purpose of the research work was to carry out the environmental evaluation and contrast of economic growth in 66 countries distributed according to their income for the period from 1994 to 2019, using data obtained from the World Bank (2021), OECD Statistics (2021), and the Pen World Table (2021) a contrast was made between the Feasible generalized least squares estimates, cointegration of Westerlund (2007), and the non-linear threshold regression model Hansen (1999), of which it was possible to verify that there are differentiated effects between these estimates, when finding threshold significance, the results indicate that economic growth leads to an increase in pollution, while environmental taxes manage to reduce it slightly. Among the main recommendations are promoting national and foreign investment of a green nature, applying and restructuring the regulatory systems for the collection of environmental taxes.